Association of CDK4 germline and BRAF somatic mutations in a patient with multiple primary melanomas and BRAF inhibitor resistance. Issue 5 (October 2015) - Governa, Maurizio; Caprarella, Evelina; Dalla Pozza, Edoardo; Vigato, Enrico; Maritan, Monia; Caputo, Glenda G.; Zannoni, Marina; Rosina, Paolo; Elefanti, Lisa; Stagni, Camilla; Menin, Chiara
<x xml:space="preserve">Abstract</x> Many genetic alterations, including predisposing or somatic mutations, may contribute toward the development of melanoma. Although CDKN2A and CDK4 are high-penetrance genes for melanoma, MC1R is a low-penetrance gene that has been associated most consistently with the disease. Moreover, BRAF is the most frequently somatically altered oncogene and is a validated therapeutic target in melanoma. This paper reports a case of multiple primary melanoma with germline CDK4 mutation, MC1R variant, and somatic BRAF mutation in nine out of 10 melanomas, indicating that a common pathogenesis, because of a predisposing genetic background, may be shared among distinct subsequent melanomas of probable clonal origin. After 3 months of targeted therapy with BRAF inhibitor, our patient developed resistance with rapid progression of the disease leading to death. This is the first case in which early resistance to BRAF inhibitor has been reported in a patient with CDK4 germline mutation.